BRANDS ARE MY LIFE, IT'S IN MY BLOOD: AN EXPLORATORY STUDY OF BRAND CONSUMPTION ON FACEBOOK FOR THE EXPRESSION OF IDENTITY - Yau, Amy Kar-Yee (2009)
This research predominantly surrounds three crucial tenets of the postmodern consumer: the consumption of brands, identity formation and the use of social networking sites (SNSs). Since these three issues combined present an unexplored area, this empirical two-part study contributing to identity theory and being conducive to industry explores the use of Facebook and brand consumption for the expression of one’s identity. The study is based on the literature in the uses and gratifications theory, identity theory and brand symbolism. In this study, a conceptual framework is proposed to understand the rationales of consuming brands on Facebook and how their views on their congruency of brands determine their construction of identity. The qualitative interpretative research enabled the interrelated issues being explored by thematically analysing 27 interviews, from social networking site (SNS) users perspective and consultancy perspective.